Quality-of-life scale machine learning approach to predict immunotherapy response in patients with advanced non-small cell lung cancer - Shen, Juanyan; Ma, Junliang; Chen, Shaolin; Jin, Su-Han; Xu, Junzhu; Li, Qisha; Zhang, Chi; Tian, Xiaojing; Chen, Xiaofei; Tan, Fangya; Hecht, Markus; Frey, Benjamin; et al. (Frontiers in Immunology, 2025)
BackgroundDespite immune checkpoint inhibitors(ICIs) significantly improve clinical outcomes in patients with advanced non-small cell lung cancer (aNSCLC), disease progression is inevitable. A diverse patient-reported Quality-of-life(QoL) scales were used to predict outcomes for aNSCLC patients with atezolizumab using machine learning.Materials and MethodsThis study analyzed the association between baseline QoL and clinical outcomes in aNSCLC patients with atezolizumab in 4 randomized clinical trials: the IMpower150 study (discovery cohort), the BIRCH, OAK and POPLAR study (validation cohorts). We identified quality of life subtypes (QoLS) by consensus clustering in the discovery cohort and predicted them in external validated cohorts.ResultsWe identified QoLS1 and QoLS2 via consensus clustering in the discovery cohort. Compared with QoLS1, QoLS2 was associated with significantly worse survival outcomes, including a shorter median overall survival (OS: 13.14 vs. 21.42 months, hazard ratio (HR) 2.07, 95% CI: 1.64 to 2.62; p < 0.0001) and progression-free survival (PFS: 5.7 vs. 8.3 months, HR 1.69, 95% CI 1.42 to 2.04; p < 0.0001). QoLS2 also was associated with lower clinical benefit rate (57% vs. 68%, p = 0.0027). In external cohorts, QoLS2 was consistently associated with unfavorable OS (p < 0.0001). Notably, QoLS1 was a positive predictive biomarker for atezolizumab efficacy: patients in QoLS1 group derived greater survival benefit from ICIs versus chemotherapy (IMpower150, p = 0.04; OAK+POPLAR, p = 0.007), while patients in QoLS2 showed no significant treatment benefit.ConclusionsOur study demonstrated the potential of integrative machine learning in effectively analyzing baseline QoL and predicting clinical outcomes in aNSCLC patients undergoing atezolizumab immunotherapy.